Corporate Governance Mechanisms, Firm Size, and Financial Performance: Evidence from Indonesian Mining Companies - Andi Muara Arumbarkah; Mahfudnurnajamuddin Mahfudnurnajamuddin; Muh. Haerdiansyah Syahnur; Muslim Muslim (Advances in Human Resource Management Research, 2026)
Purpose: This study examines the effects of institutional ownership, independent commissioners, audit committees, and firm size on the financial performance of mining companies listed on the Indonesia Stock Exchange (IDX), with Return on Assets (ROA) used as the performance indicator. Research Method: This study employed a quantitative explanatory design using audited annual report data from 30 IDX-listed mining companies during 2021–2023, generating 90 firm-year observations. The data were analyzed using multiple linear regression with SPSS after conducting classical assumption tests. Results and Discussion: Institutional ownership, independent commissioners, audit committees, and firm size have positive and significant effects on ROA. Firm size has the strongest effect, indicating that larger firms are better positioned to achieve operational efficiency, economies of scale, and broader access to financing. The positive governance effects demonstrate that effective ownership monitoring, board independence, and audit oversight strengthen managerial accountability and asset utilization. Implications: Companies should strengthen governance practices beyond formal compliance, while regulators should promote effective monitoring and accountability. Future studies should examine longer periods, other industries, additional performance measures, and governance quality indicators. Originality: This study provides sector-specific evidence from Indonesia’s mining industry on the combined role of governance mechanisms and firm size in explaining asset profitability.